Chapter Approssimazioni a Itaca e oltre (1982) o di Salgari e Torino - Curreri, Luciano (Biblioteca di Studi di Filologia Moderna, 2021)
These approximations are a tribute to Claudio Magris and his Itaca e oltre (1982), but also to Turin and to Salgari. I have attempted to push the boundaries of essay writing that, during the 1980s, was still about discovery, not scholarly archiving (or terminal editing): an essayistic form which did not shun away from drawing attention to itself, in a 'metacritical' and 'interdisciplinary' sense avant la lettre. I concentrated on a large school and said something about Marco Cerruti, with his Notizie di utopia (1985), and Pierpaolo Fornaro, whose critical narrative Trapassato presente. L'appropriazione psicologica dell'antico attraverso la narrativa moderna (1989) remains unsurpassed.